Modern Lifestyle Among Young People: A Review of S-Paylater as a Tool to Fulfill Lifestyle Needs - Salsabilla, Tasaniyah Karisma; Nopianti, Heni; Himawati, Ika Pasca (International Journal of Economics Development Research (IJEDR), 2024)
Currently, digital economy platforms offer easy access to loan services in the form of consumptive credit online, allowing users to get it quickly and without difficulty. Demographically, young people are the most likely to use buy now pay later (BNPL) digital debt services who do not yet have economic stability and are still dependent on their parents. Despite this, the urge to fulfill their lifestyle makes them continue to behave consumptively. This research focuses on the reasons that encourage young people to use spaylater as a means of fulfilling modern life styles. The research method applied is descriptive qualitative method. Data collection techniques were conducted through observation, interviews, and documentation. Informants were selected using purposive sampling involving four individuals, consisting of two FISIP UNIB students and two students outside FISIP. Data analysis was carried out through three steps, namely data reduction, data presentation, and conclusion drawing. The findings of this study indicate that young people who are students and still have economic dependence on parents use spaylater to meet the needs of a modern lifestyle. The use of spaylater among students is used as a tool to achieve their goals, namely meeting modern needs in the face of financial emergency situations.